Collaborative planning for intermodal transport with eco-label preferences. (November 2022) - Zhang, Yimeng; Heinold, Arne; Meisel, Frank; Negenborn, Rudy R.; Atasoy, Bilge
Abstract: Sustainability is a common concern in intermodal transport. Collaboration among carriers may help in reducing emissions. In this context, this work establishes a collaborative planning model for intermodal transport and uses eco-labels (a series of different levels of emission ranges) to reflect shippers' sustainability preferences. A mathematical model and an Adaptive Large Neighborhood Search heuristic are proposed for intermodal transport planning of carriers and fuzzy set theory is used to model the preferences towards eco-labels. For multiple carriers, centralized, auction-based collaborative, and non-collaborative planning approaches are proposed and compared. Real data from barge, train and truck carriers in the European Rhine-Alpine corridor is used for extensive experiments where both unimodal carrier collaboration and intermodal carrier collaboration are analyzed. Compared with non-collaborative planning without eco-labels, the number of served requests increases and emissions decrease significantly in the collaborative planning with eco-labels as transport capacity is better utilized. Highlights: A conceptual framework for collaborative planning of intermodal transport is proposed. The eco-label preferences are taken into account to achieve sustainable intermodal transport. The centralized approach, auction-based collaborative approach, and non-collaborative approaches are proposed and evaluated comparatively. Two scenarios of collaborative planning, i.e., collaboration among unimodal carriers and collaboration among intermodal carriers, are considered. Realistic transport networks in the European Rhine-Alpine corridor are used to conduct extensive experiments.